Exploring Effective Pain Relief Strategies Throughout Tonsillectomy: Before, During, and After the Surgery - Maryam Montazemi; Ali Abbaskhani Davanloo; Ali Pahnabi; Maryam Daneshian (Mazandaran University of Medical Sciences, 2023)
Background: Tonsillectomy is a common procedure for alleviating tonsil-related symptoms in children. However, postoperative pain management has remained challenging. Inadequate pain control can result in discomfort, prolonged recovery, and increased complications. This review evaluates pain management methods in tonsillectomy surgery, encompassing preoperative, intraoperative, and postoperative approaches. Methods: To gather data, a systematic search of electronic databases (PubMed, Embase, Cochrane Library) was conducted using relevant keywords to tonsillectomy, such as pain, opioid, recovery, and so on. The inclusion criteria comprised studies published in English between January 2000 and September 2022 involving pediatric and adult tonsillectomy patients. Eligible study types included randomized controlled trials, cohort studies, systematic reviews, and meta-analyses. Studies were initially screened based on titles and abstracts, followed by a full-text review. Results: Postoperative pain intensity and prevalence after tonsillectomy can vary significantly. Administering analgesics should be started before pain perception. Also, the period from the beginning of surgery to the patient's awakening is critical for optimal pain control. Delayed analgesic administration upon patient awakening may have limited efficacy. Multimodal analgesia, combining different medications with complementary mechanisms of action, is highly effective. Non-opioid analgesics such as acetaminophen and nonsteroidal anti-inflammatory drugs are commonly used alongside opioids to achieve synergistic pain relief. Regional anesthesia techniques, like peripheral nerve blocks, provide targeted pain relief and reduce systemic opioid requirements. Patient education and expectation management are vital for effective pain management. Informing patients and caregivers about the potential severity and duration of postoperative pain, as well as available pain management strategies, reduces anxiety and improves compliance. Psychological factors, including anxiety and fear, influence pain perception and tolerance, necessitating their consideration. Techniques such as cognitive-behavioral therapy, relaxation techniques, and distraction methods improve pain control and reduce anxiety. Implementing protocols of enhanced recovery after surgery (ERAS) holds promise in optimizing pain management. These protocols involve a multidisciplinary approach, including preoperative optimization, standardized pain management regimens, and early mobilization. Healthcare providers can enhance postoperative recovery and pain control in tonsillectomy patients by adopting ERAS principles. Conclusions: Effective pain management in tonsillectomy surgery necessitates a multimodal approach with preoperative analgesics, intraoperative techniques like regional anesthesia, and postoperative pain control using a combination of non-opioid and opioid medications. Patient education, addressing psychological factors, and implementing ERAS protocols are critical for optimizing pain management and improving patient outcomes in tonsillectomy surgery.